Associations between per- and polyfluoroalkyl substances exposure and renal function as well as poor prognosis in chronic kidney disease patients - Jiayin Wang; Tianyun Gao; Xiaohua Li; Ling Pan (Renal Failure)
Objectives The objectives of this study were to investigate the associations of single and mixed exposure to the environmental pollutants per- and polyfluoroalkyl substances (PFAS) with renal function and mortality in non-dialysis chronic kidney disease (CKD) patients.Methods Non-dialysis CKD1–4 stage patients in the 2003–2018 US National Health and Nutrition Examination Survey (NHANES) who were ≥20 years old were included. Five PFAS were measured and all patients were followed up till 31 December 2019. Multivariate linear, logistic, and Cox regressions were used to evaluate the associations between PFAS exposure and renal function, mortality. Stratified subgroups were analyzed based on baseline characteristics. Bayesian kernel machine regression (BKMR) was used in sensitivity analysis.Results Among 1503 CKD patients included, baseline renal function declined in 701 patients (44.4%) and 462 patients (24.9%) died during the follow-up. Single exposure to perfluorooctanoic acid (PFOA), perfluorooctane sulfonic acid (PFOS), perfluorononanoic acid (PFNA), and perfluorohexane sulfonic acid (PFHxS) was positively associated with renal function decline (p < .05). Mixed exposure to five kinds of PFAS was found to be associated with renal function decline. Restricted cubic spline (RCS) showed only PFOS had an inverted U-shaped association with renal function decline (p non-linear < .05). There was no statistically significant association between PFAS exposure and mortality. Urinary protein and drug use might interact with the associations between PFAS and renal function.Conclusions PFAS single and mixed exposure were closely related to renal function and renal progression in adult CKD patients. There was no statistically significant association between PFAS exposure and mortality.